Comparing the Greek Phalanx with the Roman Legion - Kochom, Garrett (My University, 2010)
This study examined the Republican Roman field armies (circa 218-168 BCE) to establish their tactical organization and deployment strategies in order to determine how significant it was to their success. The Greeks used armies of massed infantry standing very close together, all joined as one giant unit. The Romans, however, pioneered small-unit tactics, and organized their armies into smaller formations capable of acting independently of the rest of the army. This made the the legions extremely versatile in battle when compared to the phalanx.
More Than a Handful is Too Much : an Examination of Republican Roman Battle Tactics
Color poster with text and images.
Keywords: Greece. Stratos--Drill and tactics; Rome--Army--Drill and tactics; Military art and science--Greece; Posters; Military art and science--Rome